No Sexual Dimorphism Detected in Digit Ratios of the Fire Salamander (Salamandra salamandra). Issue 10 (10th August 2015) - Balogová, Monika; Nelson, Emma; Uhrin, Marcel; Figurová, Mária; Ledecký, Valent; Zyśk, Bartłomiej
ABSTRACT It has been proposed that digit ratio may be used as a biomarker of early developmental effects. Specifically, the second‐to‐fourth digit ratio (2D:4D) has been linked to the effects of sex hormones and their receptor genes, but other digit ratios have also been investigated. Across taxa, patterns of sexual dimorphism in digit ratios are ambiguous and a scarcity of studies in basal tetrapods makes it difficult to understand how ratios have evolved. Here, we focus on examining sex differences in digit ratios (2D:3D, 2D:4D, and 3D:4D) in a common amphibian, the fire salamander (Salamandra salamandra). We used graphic software to measure soft tissue digit length and digit bone length from X‐rays. We found a nonsignificant tendency in males to have a lower 2D:3D than females; however, no sexual differences were detected in the other ratios. We discuss our results in the context of other studies of digit ratios, and how sex determination systems, as well as other factors, might impact patterns of sexual dimorphism, particularly in reptiles and in amphibians. Our findings suggest that caution is needed when using digit ratios as a potential indicator of prenatal hormonal effects in amphibians and highlight the need for more comparative studies to elucidate the evolutionary and genetic mechanisms implicated in sexually dimorphic patterns across taxonomic groups. Anat Rec, 298:1786–1795, 2015. © 2015 Wiley Periodicals, Inc.